The diffusion equation with piecewise smooth initial conditions - Ashurov, Ravshan; Butaev, Almaz (Universiti Putra Malaysia Press, 2011)
In this paper we consider an initial-value problem for diffusion equation in three dimensional Euclidean space. The initial value is a piecewise smooth function. To solve this problem we apply Fourier transform method and since Fourier integrals of a piecewise smooth function do not converge everywhere, we make use of Riesz summation method.